Mucopolysaccharidosis type IIIB: a current review and exploration of the AAV therapy landscape - Courtney J Rouse; Victoria N Jensen; Coy D Heldermon (Neural Regeneration Research, 2024)
Mucopolysaccharidoses type IIIB is a rare genetic disorder caused by mutations in the gene that encodes for N-acetyl-alpha-glucosaminidase. This results in the aggregation of heparan sulfate polysaccharides within cell lysosomes that leads to progressive and severe debilitating neurological dysfunction. Current treatment options are expensive, limited, and presently there are no approved cures for mucopolysaccharidoses type IIIB. Adeno-associated virus gene therapy has significantly advanced the field forward, allowing researchers to successfully design, enhance, and improve potential cures. Our group recently published an effective treatment using a codon-optimized triple mutant adeno-associated virus 8 vector that restores N-acetyl-alpha-glucosaminidase levels, auditory function, and lifespan in the murine model for mucopolysaccharidoses type IIIB to that seen in healthy mice. Here, we review the current state of the field in relation to the capsid landscape, adeno-associated virus gene therapy and its successes and challenges in the clinic, and how novel adeno-associated virus capsid designs have evolved research in the mucopolysaccharidoses type IIIB field.